2017
DOI: 10.7126/cumudj.369035
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diode Laser as an Adjunct to Periodontal Treatment on Clinical Periodontal Parameters and Halitosis: A Randomized Controlled Clinical Trial

Abstract: Conclusion:The present study indicates that compared to SRP solely, adjunctive applications of a 940-nm diode laser with SRP showed lower bleeding on probing and halitosis levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…In seven articles, the use of local anaesthesia in conjunction with periodontal treatment was reported (Dereci et al, ; Eltas & Orbak, ; Euzebio Alves et al, ; Hatipoglu et al, ; Kamma et al, ; Matarese et al, ; Üstün et al, ); in one article, local anaesthesia was reported to be delivered if needed (Rotundo et al, ) whereas lack of information with respect to the use of local anaesthesia was observed in two articles (Dilsiz et al, ; Kelbauskiene et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In seven articles, the use of local anaesthesia in conjunction with periodontal treatment was reported (Dereci et al, ; Eltas & Orbak, ; Euzebio Alves et al, ; Hatipoglu et al, ; Kamma et al, ; Matarese et al, ; Üstün et al, ); in one article, local anaesthesia was reported to be delivered if needed (Rotundo et al, ) whereas lack of information with respect to the use of local anaesthesia was observed in two articles (Dilsiz et al, ; Kelbauskiene et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 10 articles evaluating the adjunctive use of laser are summarized in Table 2 (Dereci, Hatipoglu, Sindel, Tozoglu, & Üstün, 2016;Dilsiz, Canakci, & Aydin, 2013;Eltas & Orbak, 2012a;Euzebio Alves et al, 2013;Hatipoglu et al, 2017;Kamma, Vasdekis, & Romanos, 2009;Kelbauskiene, Baseviciene, Goharkhay, Moritz, & Machiulskiene, 2011;Matarese, Ramaglia, Cicciu, Cordasco, & Isola, 2017;Rotundo et al, 2010;Üstün, Hatipoglu, Daltaban, Felek, & Firat, 2018).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of the participant number were as follows: from 11 to 20 in two studies, 45 , 47 from 21 to 50 in eleven studies 42–44 , 46 , 48 , 49 , 51 , 53–56 and from 51 to 60 participants in two studies 50 , 52 ( Table 1 ), whereas the distribution of the subjects’ number according to gender is illustrated in Figure 2 for only 11 of the 15 studies, whereas four studies failed to document the gender of their participants. 45 , 47 , 52 , 56
Figure 2 Illustrates the percentage of the gender distribution according to the number of the recruited subjects.
…”
Section: Resultsmentioning
confidence: 99%
“…4 One common therapy in the treatment of periodontitis is the topical application of antimicrobial therapy and hyaluronic acid. 5,6 Hyaluronic acid (HA) can weaken the bonds of chronic inflammatory tissue cells with the result that they are readily released and replaced through the regeneration of healthy cells. It also produces antimicrobial effects on Aggregatibacter actinomycetemcomitans, Provotela oris, Porphyromonas gingivalis and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%